Pemberdayaan Kader Kesehatan tentang Pentingnya 1000 Hari Pertama Kehidupan (1000 HPK) dalam Pencegahan Stunting dan Pencegahan Malaria pada ibu hamil di Kampung Bibiosi Distrik Arso Kabupaten Keerom - Wahyuni, Sri; Heni Voni Rerey; Martina Mogan (Rena Cipta Mandiri, 2025)
Stunting is a chronic nutritional problem that affects the quality of human resources. Stunting prevention efforts need to focus on the First 1,000 Days of Life (1000HPK), from pregnancy to two years of age. Approximately 468–469 children under five in Keerom Regency are suspected of experiencing stunting. Malaria during pregnancy can lead to anemia, low birth weight, and other pregnancy complications if not properly managed. Health cadres play a strategic role in providing education and support to the community. This community service activity aims to empower health cadres by increasing their knowledge and understanding of the importance of the 1000HPK in stunting prevention and how cadres can provide counseling to pregnant women about malaria prevention. The methods used included counseling, interactive discussions, and evaluation of cadre knowledge. The activity results showed an increase in the knowledge of 15 cadres regarding the concept of the 1000HPK, stunting risk factors, and the role of cadres in stunting prevention efforts in the community. Furthermore, there was an increase in cadre knowledge regarding malaria prevention efforts in pregnant women.